The Effect of Glycerol on the Production of Environmentally Friendly Bioplastics From Cassava Peel (Manihot Esculenta) and Corn Cobs (Zea Mays) - Merliana Christmas Turangan; Helen Joan Lawalata; Utari Satiman; Rievo Handry Djarang (Journal of Comprehensive Science, 2026)
Conventional plastics made from synthetic polymers have a low biodegradation rate, which contributes greatly to environmental pollution. The use of agricultural waste such as cassava husks (Manihot esculenta) and corn cobs (Zea mays) as bioplastic raw materials is one of the alternatives for the development of environmentally friendly materials. This study aims to determine the effect of variations in the amount of glycerol and the length of decomposition time on the biodegradability of bioplastics made from cassava husks and corn cobs. The study used an experimental method with a Two-Way Factorial Design, covering three concentrations of glycerol (0 mL, 15 mL, and 30 mL) and three decomposition times (3, 6, and 9 days). The results showed that the treatment without glycerol (0 mL) did not form bioplastics so it could not be analyzed. The data was tested using Two Way ANOVA. The results of the biodegradability test showed that the glycerol concentration had a significant effect, and the 30 mL formulation resulted in the highest degradation rate of 91.026% on day 9.